Effects of surgical removal of mandibular third molar on the periodontium of the second molar - AJP Chaves (Journal compilation 2008 Blackwell Munksgaard, 2008)
The effects on periodontal tissues of adjacent second molars after semi-impacted mandibular third molar surgery were evaluated.